EXPLORE THE ROLES OF FEMALE ENTREPRENEURSHIP IN PROMOTING ECONOMIC GROWTH IN ASIA: A PANEL DATA ANALYSIS - Binh, Hoang Xuan; Pham, Huong-Giang; Nguyen, Khanh Ly T. (International Journal of Application on Economics and Business, 2024)
In Asia, there has been a notable surge in the representation of women in leadership roles and entrepreneurial endeavours, aligning with the increasing acknowledgement of women's importance in politics and the economy. It is predicted that the future development and economic prosperity of Asia will heavily rely on the advancement of female entrepreneurship and empowerment. This research aims to provide empirical evidence on the correlation between female entrepreneurship and economic advancement within the diverse landscape of Asia context, using panel data spanning from 1998 to 2021 across 47 Asian countries. The findings of fixed-effect regression reveal a consistently positive association between women's entrepreneurial activities and economic progress across all Asian economies, encompassing both developed and developing nations. These findings are pivotal for crafting tailored policies aimed at enhancing female participation in entrepreneurship, thereby catalyzing economic growth and advancing towards the most potential in terms of socio-economic conditions.